Cash Flow and Accrual Anomalies: Evidence from Borsa Istanbul - Kaya, Emine (The Indonesian Capital Market Review, 2022)
This study aims to determine the persistence of earning and its components and whether investors accurately evaluate the information related to the earning and its components. The study covers the firms operating in Borsa Istanbul between 2005-2017 time period. We sort the accruals and cash flows into five portfolios. Then, we employ linear regression and Mishkin test estimations. Moreover, we compare the asset pricing models with nine metrics in explaining the cash flow and accrual anomalies. Linear regression and Mishkin test estimations show that the persistence of earning is high. The other finding is that cash flow and accrual do not correctly reflect on the stock prices. Also, our results show that the financial asset pricing model is successful in explaining the cash flow and the accrual anomalies. As a result, we can see that the financial asset pricing model continues to be an important model in explaining asset prices. On the other hand, our study is different from the other studies since it uses the Fama and French Five Factor Model to determine the cash flow and accrual anomalies.